Financial Literacy Importance in Personal Finance Management - Musiał, Marta (Journal of Finance and Financial Law, 2016)
The purpose of this article is to demonstrate a low level of financial literacy among Poles living in the biggest Polish cities. Moreover, based on research we attempt to verify the following hypotheses. First hypothesis assumes that the level of financial knowledge is conditioned by demographic and social factors, i.e. gender, age or education. The second hypothesis is that there is a relation between peopleʼs financial knowledge and financial factors, i.e. income, expenses and savings of their household.